(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Land and houses, as peoplell as natural resources such as crops, minerals, and water, make up real estate. The value of a residential property in the housing market is determined by how it is designed, the landscape, and house characteristics. This is important for urban planning and community growth. Without knowing anything about the market value by analyzing the attributes of the properties people may be manipulated into buying at a higher price or selling at a lo peopler price. Using the data of residential properties which consists of different attributes like street name, city, Area sqft, price etc. Authors are going to use big data approach to analyze, store and view data. people’ll be also using an algorithm to predict the market value so that people can know about the market values to avoid getting manipulated.